Pengaruh Kecemasan Ujian Menggunakan Google Form Terhadap Hasil Belajar Di SMA Negeri 11 Makassar - Masikki; Wirawan Setialaksana; Nur Aini Anis (Information Technology Education Journal, 2024)
Abstract- This research aims to determine the effect of exam anxiety using Google Form on the learning outcomes of students at SMA Negeri 11 Makassar. This type of research is quantitative research. Quantitative Method because information or data is represented numerically and analyzed statistically. The population in this study were all students of SMA Negeri 11 Makassar class X, XI, and XII. The sample used in this research was 317 students taken using proportional sampling technique. The research results show that exam anxiety using Google Form is in the medium category with a percentage value of 75.71% and student learning outcomes are in the medium category with a percentage value of 69.40%. Based on this, there is a negative and significant influence between exam anxiety using Google Forms on student learning outcomes.